Effect of soils reinforced with PET waste in reducing loads transferred to buried pipeline - Aksoy, Huseyin Suha; Bitkin, Rifat Enes (Keai Publishing Ltd, 2026)
Buried pipelines need to limit the surface loads transferred on them in order to ensure trouble-free operation throughout their service life. The objective of this study was to evaluate the efficacy of PET waste as a reinforcing material in mitigating the pressure exerted on buried pipes due to surface loading. The experimental program involved a series of model tests carried out on pipes embedded in sand, where the soil layers surrounding the pipes were reinforced with varying amounts of PET waste (1 %, 3 %, and 5 % by weight). The influence of reinforcement at different PET content levels and layer thicknesses on key parameters such as bearing capacity, foundation settlement, and strain distribution at critical points (crown, springline, and invert) of the pipe was assessed and compared to unreinforced condition. The findings showed that the reinforcement of PET waste significantly enhanced the bearing capacity of the foundation and reduced the loading stresses transferred to the pipe's crown and springline. Specifically, the reinforced configurations exhibited up to a 90 % increase in bearing capacity and up to a 50 % reduction in strain at the crown relative to the unreinforced tests. Furthermore, an increase in the depth of the PET-reinforced layer correlated with a higher bearing capacity and a further decrease in strain values at the pipe's surface. This comprehensive experimental analysis highlights the potential of PET waste reinforcement as a feasible and effective method to reduce stresses transferred to buried pipes.
Keywords: Buried Pipes; Soil Reinforcement; Pet Waste; Bearing Capacity; Strain